Strain‐Induced Orbital Contributions to Oxygen Electrocatalysis in Transition‐Metal Perovskites. Issue 46 (24th October 2021) - Fernandez, Abel; Caretta, Lucas; Das, Sujit; Klewe, Christoph; Lou, Djamila; Parsonnet, Eric; Gao, Ran; Luo, Aileen; Shafer, Padraic; Martin, Lane W.
Abstract: Epitaxial strain has been shown to produce dramatic changes to the orbital structure in transition metal perovskite oxides and, in turn, the rate of oxygen electrocatalysis therein. Here, epitaxial strain is used to investigate the relationship between surface electronic structure and oxygen electrocatalysis in prototypical fuel cell cathode systems. Combining high‐temperature electrical‐conductivity‐relaxation studies and synchrotron‐based X‐ray absorption spectroscopy studies of La0.5 Sr0.5 CoO3 and La0.8 Sr0.2 Co0.2 Fe0.8 O3 thin films under varying degrees of epitaxial strain reveals a strong correlation between orbital structure and catalysis rates. In both systems, films under biaxial tensile strain simultaneously exhibit the fastest reaction kinetics and lowest electron occupation in the dz 2 orbitals. These results are discussed in the context of broader chemical trends and electronic descriptors are proposed for oxygen electrocatalysis in transition metal perovskite oxides. Abstract : Combining high‐temperature electrical‐conductivity‐relaxation and X‐ray absorption spectroscopy studies of epitaxially strained La0.5 Sr0.5 CoO3 and La0.8 Sr0.2 Co0.2 Fe0.8 O3 thin films reveals a strong correlation between orbital structure and catalysis rates. Films under biaxial tensile strain exhibit the fastest reaction kinetics and lowest electron occupation in the d z 2 orbitals. The results highlight the importance of the d z 2 orbitals for oxygen electrocatalysis in perovskite thin films.